Kepatuhan Hand Hygiene dan Pengetahuan Perawat Tentang Healthcare Associated Infections (HAIs) di Ruangan Intensif Rumah Sakit Santa Elisabeth Medan - Lilis Novitarum; Lindawati Simorangkir; Samfriati Sinurat; Vivi Labora Malau (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Healthcare Associated Infections (HAIs) are serious occurrences and problems that are often found in all hospital facilities. HAIs cause extended hospitalization, permanent disability, increased treatment costs, and death. Hand Hygiene has an important role in the prevention and control of HAIs. This study aims to see the compliance of nurses' hand hygiene and nurses' knowledge of healthcare associated infections (HAIs) in the intensive care unit of Santa Elisabeth Hospital Medan in 2024. The type of research design used was descriptive with a sampling technique using a total of 31 respondents. Based on the results of the study, it was found that most nurses were obedient in carrying out hand hygiene (83.9%) and knowledge that is about the prevention of HAIs was found to be a large number of nurses who had high knowledge (67.7%). It is hoped that nurses maintain compliance in performing hand hygiene so that HAIs do not occur.